A Defective Interfering Influenza RNA Inhibits Infectious Influenza Virus Replication in Human Respiratory Tract Cells: A Potential New Human Antiviral - Smith, Claire; Scott, Paul; O’Callaghan, Christopher; Easton, Andrew; Dimmock, Nigel (Viruses, 2016)
Defective interfering (DI) viruses arise during the replication of influenza A virus and contain a non-infective version of the genome that is able to interfere with the production of infectious virus. In this study we hypothesise that a cloned DI influenza A virus RNA may prevent infection of human respiratory epithelial cells with infection by influenza A. The DI RNA (244/PR8) was derived by a natural deletion process from segment 1 of influenza A/PR/8/34 (H1N1); it comprises 395 nucleotides and is packaged in the DI virion in place of a full-length genome segment 1. Given intranasally, 244/PR8 DI virus protects mice and ferrets from clinical influenza caused by a number of different influenza A subtypes and interferes with production of infectious influenza A virus in cells in culture. However, evidence that DI influenza viruses are active in cells of the human respiratory tract is lacking. Here we show that 244/PR8 DI RNA is replicated by an influenza A challenge virus in human lung diploid fibroblasts, bronchial epithelial cells, and primary nasal basal cells, and that the yield of challenge virus is significantly reduced in a dose-dependent manner indicating that DI influenza virus has potential as a human antiviral.